Czy można racjonalnie nie wierzyć w ewolucję? Analiza argumentacji Alvina Plantingi - Pepliński, Marek (Filozofia Nauki, 2001)
Alvin Plantinga claims that Christian believer can rationally disbelieve in some elements of the theory of evolution: the Common Ancestry Thesis; Darwinism, taken as explanation of origin of life by the mechanism of natural selection operating on random genetic mutation, and Naturalistic Origins Thesis - the view that present life itself developed from nonliving matter without special activity of God. After the justification of the possibility of conflicts between faith and science, Plantinga's arguments are examined and assessed as successful, with a few exceptions. The main thesis of this paper is that Plantinga is right claiming that rational disbelieving in evolution is possible, but his arguments are not enough to justify special creationism as theistic knowledge, supposing that knowledge warrants the truth.